2013
DOI: 10.1002/psc.2579
|View full text |Cite
|
Sign up to set email alerts
|

BOP‐OXy, BOP‐OBt, and BOP‐OAt: novel organophosphinic coupling reagents useful for solution and solid‐phase peptide synthesis

Abstract: Stand-alone coupling reagents derived from bis(2-oxo-3-oxazolidinyl)phosphorodiamidic chloride show efficient performance in solution and SPPS. In particular, the Oxyma Pure (Luxembourg Biotech., Tel Aviv, Israel) derivative shows the additional advantage of being highly soluble in DMF and even fairly soluble in CH3 CN, which can extend its use for the synthesis of complex peptides. These new stand-alone coupling reagents have the advantage of not bearing any counteranion such as PF6 or BH4 , whose presence ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…They also developed another derivative by combining Oxyma with bis (2-oxo-3-oxazolidinyl) phosphorodiamidic chloride (BOP-Cl). Through their tests, they found that the use of BOP-Oxy 43 is advantageous in most cases because of the higher coupling efficiency and more efficient suppression of racemization [57].…”
Section: Amide Bond Formationmentioning
confidence: 97%
“…They also developed another derivative by combining Oxyma with bis (2-oxo-3-oxazolidinyl) phosphorodiamidic chloride (BOP-Cl). Through their tests, they found that the use of BOP-Oxy 43 is advantageous in most cases because of the higher coupling efficiency and more efficient suppression of racemization [57].…”
Section: Amide Bond Formationmentioning
confidence: 97%
“…PEGylated lactobionic acid targeted honokiol G 3 piperazine dendrimer conjugate (TPG 3 À OH)-HK-LA-PEG was prepared via carbodiimide coupling reaction. In the first step, the thirdgeneration triazine dendrimer (TPG 3 À OH) 10 was preactivated with 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC•HCl) in the presence of potassium salt of Oxyma as coupling reagent in acetonitrile/water mixed solvent for 5 minutes, [77][78][79][80][81][82][83][84][85] followed by addition of honokiol (HK). The reaction mixture was stirred overnight.…”
Section: Synthesis Of Peg-lactobionic Acid-honokiol-hexadeca Carboxylic Acid G 3 -Triazine Dendrimer Conjugate (Tpg 3 à Oh)-hk-la-pegmentioning
confidence: 99%
“…In 2014, our group reported novel Oxyma-based organophosphorus reagents for coupling reactions. 54 The nucleophilic additives HOBt, HOAt, OxymaPure and N-Oxyma (carboxamide instead of ethyl ester) reacted with BOP-Cl in the presence of Et 3 N, forming the corresponding phosphinic reagent (Scheme 12). Among these reagents, BOP-Oxy showed higher solubility in DMF and MeCN.…”
Section: Oxyma-based Phosphatesmentioning
confidence: 99%